The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1017/s0033291704002442
|View full text |Cite
|
Sign up to set email alerts
|

Personality characteristics of women before and after recovery from an eating disorder

Abstract: Women with eating disorders in both the ill and recovered state show higher levels of harm avoidance and lower self-directedness and cooperativeness scores than normal control women. Although findings suggest that disturbances may be trait-related and contribute to the disorders' pathogenesis, additional research with more representative community controls, rather than our pre-screened, normal controls, is needed to confirm these impressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
124
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 168 publications
(141 citation statements)
references
References 49 publications
15
124
0
2
Order By: Relevance
“…Finally, dysthymia and OCD were reported significantly more often in probands with PAN than in those with RAN. Together these findings are consistent with observations 34 that the presence of binge eating and purging is associated with greater comorbidity and underscore the importance of developing analytic plans for linkage that carefully attend to the presence of binge eating in this sample.…”
Section: Resultssupporting
confidence: 87%
“…Finally, dysthymia and OCD were reported significantly more often in probands with PAN than in those with RAN. Together these findings are consistent with observations 34 that the presence of binge eating and purging is associated with greater comorbidity and underscore the importance of developing analytic plans for linkage that carefully attend to the presence of binge eating in this sample.…”
Section: Resultssupporting
confidence: 87%
“…Studies comparing actively ill with recovered individuals have indicated that anxiety and certain temperamental traits persist beyond recovery. 37,38 Based on our sample, individuals with a diagnosis of PAN have a higher likelihood of exercising excessively and are therefore more likely to have the associated clinical and personality variables. These results suggest that excessive exercise may be a central strategy that contributes to maintenance of low BMI in patients with AN.…”
Section: Resultsmentioning
confidence: 99%
“…Someone with this diagnosis is frequently constrained, conforming, obsessional, rigid, and perfectionistic" (p. S69). To demonstrate, we present a vignette of an individual with AN ( Figure 2) drawn from an historical account from 1866 (cited in Brumberg, 1988) to highlight features extensively documented in AN both premorbidly and following weight restoration: cognitive and behavioral rigidity (Anderluh et al, 2003;, perfectionism (Bastiani, Rao, Weltzin, & Kaye, 1995;Bulik et al, 2003;Halmi et al, 2000;Woodside et al, 2002), social withdrawal (Diaz-Marsa, Carrasco, & Saiz, 2000; I. C. Gillberg et al, 1995;Godart et al, 2004;Holliday, Uher, Landau, Collier, & Treasure, 2006;Karwautz, Troop, Rabe-Hesketh, Collier, & Treasure, 2003;Kaye et al, 2004), constriction (Geller, Cockell, Hewitt, Goldner, & Flett, 2000), and harm avoidance (Diaz-Marsa et al, 2000;Klump et al, 2000Klump et al, , 2004. In fact, the reliable presentation of this behavioral and personality cluster has been demonstrated to add to the incremental validity of diagnostic accuracy (Westen & Harnden-Fischer, 2001).…”
Section: Overview Of the Phenotypic Expression Of Anmentioning
confidence: 99%